2021
DOI: 10.1039/d1ra05737e
|View full text |Cite|
|
Sign up to set email alerts
|

The role of substituted pyridine Schiff bases as ancillary ligands in the optical properties of a new series of fac-rhenium(i) tricarbonyl complexes: a theoretical view

Abstract: Over the last few years, luminescent Re(i) tricarbonyl complexes have been increasingly proposed as fluorophores suitable for fluorescence microscopy to visualize biological structures and cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 110 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…By contrast, PSB2 to PSB4 present the −OH in the ortho position with respect to the azomethine link, which would favor the formation of the IHB. Since the presence of highly electronegative halogens (F or Cl) vicinal to −OH impairs the formation of IHB, apparently acting as a switch between the visible and NIR emissions, 11 we wanted to determine whether the presence of other halogens can disrupt the IHB, potentially affecting the emission. Thus, we are interested in comparing Re(I) complexes (Figure 1) concerning their predicted absorption and emission, Stoke's shift, and luminescent lifetimes (τ), among other characterizations aimed to better understand the role of the IHB in the emission modulation.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, PSB2 to PSB4 present the −OH in the ortho position with respect to the azomethine link, which would favor the formation of the IHB. Since the presence of highly electronegative halogens (F or Cl) vicinal to −OH impairs the formation of IHB, apparently acting as a switch between the visible and NIR emissions, 11 we wanted to determine whether the presence of other halogens can disrupt the IHB, potentially affecting the emission. Thus, we are interested in comparing Re(I) complexes (Figure 1) concerning their predicted absorption and emission, Stoke's shift, and luminescent lifetimes (τ), among other characterizations aimed to better understand the role of the IHB in the emission modulation.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 99%
“…11 Recently, it has been shown that the presence of a strongly electronegative halogen (F or Cl) in position 6 visible range to the NIR range. 11 These results suggest a role of the IHB as an important switcher between visible and NIR emissions in this kind of complexes. Since PSBs can be substituted to modulate the properties of the whole Re(I) complex, it is necessary to explore whether other substitutions can also affect the photophysical properties, mainly the emission range.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations